1989
DOI: 10.1159/000158777
|View full text |Cite
|
Sign up to set email alerts
|

Caffeine-Induced Contraction in Arteries from Stroke-Prone Spontaneously Hypertensive Rats

Abstract: Differences in caffeine-induced contraction in smooth muscle of resistance vessels from stroke-prone spontaneously hypertensive rats (SHRSP) and Wistar Kyoto rats (WKY) were investigated by using mesenteric artery preparations. The contraction induced by caffeine (10 mM) was greater in SHRSP preparations, both in the presence and absence of Ca (10 min after Ca removal). Caffeine-induced contraction was gradually decreased by the removal of extracellular Ca. No significant difference was observed in the time co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

1997
1997
2017
2017

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 17 publications
(22 reference statements)
0
7
0
Order By: Relevance
“…A larger contraction induced by caffeine has also been reported in the small mesenteric arteries from stroke-prone SHR (SHRSP) (24) and in the aorta (17), femoral artery (9) and carotid artery (19) from SHR. In the tail artery the caffeine contraction was the same for the two strains (20).…”
Section: Discussionmentioning
confidence: 81%
“…A larger contraction induced by caffeine has also been reported in the small mesenteric arteries from stroke-prone SHR (SHRSP) (24) and in the aorta (17), femoral artery (9) and carotid artery (19) from SHR. In the tail artery the caffeine contraction was the same for the two strains (20).…”
Section: Discussionmentioning
confidence: 81%
“…Early studies found that caffeine-induced contraction of mesenteric resistance arteries (1033) and aortas (727) is increased in vessels from SHRSP versus WKY rats and that this is likely due to an increased Ca 2+ load in the SR (727). RyR function also appears to be enhanced in SMCs from SHR versus WKY rats (276).…”
Section: Ryanodine Receptorsmentioning
confidence: 99%
“…Caffeine produced transient contractions of arterial smooth muscle at millimolar concentrations in vitro (Kalsner, 1971;Karaki et al, 1987;Sato et al, 1988;Moriyama et al, 1989), which were more marked in preparations from spontaneously hypertensive rats than from normotensive rats (Moriyama et al, 1989). Caffeine-induced vascular contractions were reduced or blocked by removal of extracellular calcium or by the inhibition of calcium release from the sarcoplasmic reticulum (Sato et al, 1988;Moriyama et al, 1989).…”
Section: Vascular Effects and Calciummentioning
confidence: 99%
“…Caffeine-induced vascular contractions were reduced or blocked by removal of extracellular calcium or by the inhibition of calcium release from the sarcoplasmic reticulum (Sato et al, 1988;Moriyama et al, 1989). It has been suggested that the mobilization of intracellular calcium by the so-called calciuminduced calcium release mechanism is crucial in caffeineinduced vasoconstriction (Karaki et al, 1987).…”
Section: Vascular Effects and Calciummentioning
confidence: 99%